Developing sustainability indicators for the Kogelberg and Cape West Coast Biosphere Reserves, South Africa - Tucker, Colin Michael (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScConEcol)--Stellenbosch University, 2013.